"An absolutely necessary piece": A qualitative study of legal perspectives on medical affidavits in the asylum process. (November 2016) - Scruggs, Elizabeth; Guetterman, Timothy C.; Meyer, Anna C.; VanArtsdalen, Jamie; Heisler, Michele
Abstract: A key challenge for asylum seekers in the United States is being able to provide evidence of prior persecution in their home countries. Medical/psychological affidavits corroborating applicants' accounts often make the difference between successful and unsuccessful applications. The purpose of this study was to identify the unmet demand for and features of effective medical/psychological affidavits in the asylum process, as well as the personal and systemic barriers for asylum seekers. This is a qualitative study of semi-structured interviews with legal professionals who work in asylum law. Sixteen asylum lawyers and one Board of Immigration Appeals accredited representative practicing in the state of Michigan, United States, participated in this study. All participants noted that a vast majority of their asylum cases would benefit from a medical affidavit but that they have difficulty finding qualified physicians with experience writing such affidavits and testifying as expert witnesses. The major barriers to obtaining medical/psychological evaluations included inability to pay for services, lack of practitioner availability, and lack of practitioner training. The participants reported that features of a strong medical affidavit included clear, concise, and corroborative accounts that supported the applicant's story from a diagnostic perspective and forensic descriptions that reinforced the credibility of the applicant. Several also noted that medical/psychological evaluations frequently would reveal additional details and incidents of trauma beyond those stated in the applicant's preliminary statement. The study results suggest substantial unmet need for trained physicians to perform medical and psychological evaluations on a pro bono basis. Lawyers' recommendations regarding effective medical affidavits and necessary ongoing support for asylum applicants should inform current efforts to improve physician and lawyer collaborations on asylum cases. Highlights: Trained physicians are needed to perform medical/psychological evaluations on a pro bono basis. Barriers to asylum seekers include financial constraints and practitioner availability. Strong medical affidavits provide corroborative accounts from a diagnostic perspective. Medical/psychological evaluations sometimes reveal additional detail and incidents of trauma. Lawyers' recommendations inform future medical-legal collaborations on asylum cases.